The HUSH complex cooperates with TRIM28 to repress young retrotransposons and new genes - Robbez-Masson, Luisa; Tie, Christopher H.C.; Conde, Lucia; Tunbak, Hale; Husovsky, Connor; Tchasovnikarova, Iva A.; Timms, Richard T.; Herrero, Javier; Lehner, Paul J.; Rowe, Helen M.

(untitled) (Genome Research, 2018)
Retrotransposons encompass half of the human genome and contribute to the formation of heterochromatin, which provides nuclear structure and regulates gene expression. Here, we asked if the human silencing hub (HUSH) complex is necessary to silence retrotransposons and whether it collaborates with TRIM28 and the chromatin remodeler ATRX at specific genomic loci. We show that the HUSH complex contributes to de novo repression and DNA methylation of an SVA retrotransposon reporter. By using naïve versus primed mouse pluripotent stem cells, we reveal a critical role for the HUSH complex in naïve cells, implicating it in programming epigenetic marks in development. Although the HUSH component FAM208A binds to endogenous retroviruses (ERVs) and long interspersed element-1s (LINE-1s or L1s), it is mainly required to repress evolutionarily young L1s (mouse-specific lineages <5 million years old). TRIM28, in contrast, is necessary to repress both ERVs and young L1s. Genes co-repressed by TRIM28 and FAM208A are evolutionarily young, or exhibit tissue-specific expression, are enriched in young L1s, and display evidence for regulation through LTR promoters. Finally, we demonstrate that the HUSH complex is also required to repress L1 elements in human cells. Overall, these data indicate that the HUSH complex and TRIM28 co-repress young retrotransposons and new genes rewired by retrotransposon noncoding DNA.